2011
DOI: 10.5664/jcsm.1318
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Epilepsy and Parental Sleep Quality

Abstract: Study Objectives: To evaluate the effects of pediatric epilepsy on sleep in parents of epileptic children. Methods: Cohort design in which the sleep quality of parents of epileptic children (POEC) and parents of nonepileptic children (PONEC) in the month preceding recruitment were compared using the self-administered Pittsburgh Sleep Quality Index (PSQI). Results: Mothers of epileptic children had a 7-fold occurrence of sleep disturbances when compared to mothers of non-epileptic children (OR = 6.66 CI 95% 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 19 publications
2
47
1
1
Order By: Relevance
“…The study also advised that larger, more methodological rigorous research should be performed. Shaki, Goldbart, Daniel, Fraser, and Shorer (2011) were able to support these overall findings when they evaluated sleep disturbances in a cohort of parents of epileptic children against a cohort of parents of nonepileptic children. Each group of parents was administered the PSQI, a subjective self-administered questionnaire that measures nighttime sleep quality, that reflected the month before participation in the study.…”
Section: Journal Of Neuroscience Nursingsupporting
confidence: 60%
“…The study also advised that larger, more methodological rigorous research should be performed. Shaki, Goldbart, Daniel, Fraser, and Shorer (2011) were able to support these overall findings when they evaluated sleep disturbances in a cohort of parents of epileptic children against a cohort of parents of nonepileptic children. Each group of parents was administered the PSQI, a subjective self-administered questionnaire that measures nighttime sleep quality, that reflected the month before participation in the study.…”
Section: Journal Of Neuroscience Nursingsupporting
confidence: 60%
“…While both parents are, inevitably, affected by onset of epilepsy in their children [26,27], it seems that mothers sustain a greater burden of care for the child [28]. In line with previous studies, it has been indicated that mothers demonstrate higher levels of strain and more sleep disturbances compared with fathers [17,29]. Because of this, it is likely that mothers become more involved in seizure-related issues.…”
Section: Discussionmentioning
confidence: 60%
“…Dørheim, Bondevik, Eberhard-Gran, & Bjorvatn, 2009), culturally diverse postpartum samples (Li et al, 2011), and postpartum depression (b. Dørheim, Bondevik, Eberhard-Gran, & Bjorvatn, 2009; Okun, Hanusa, Hall, & Wisner, 2009; Okun, Luther, Prather, Perel, Wisniewski, & Wisner, 2011); it has also been used among caregiving fathers (Shaki, Goldbart, Daniel, Fraser, & Shorer, 2011). …”
Section: Methodsmentioning
confidence: 99%